The relationship among intrinsic leisure motivation, social support, and perceived wellness for the people who aged over 65 years - Cheng-Yu Tsai; Pahrudin Pahrudin; Ming-Tsang Wu (Cogent Social Sciences, 2024)
The study aims to examine the relationship between intrinsic leisure motivation, social support, and perceived wellness among the people who aged over 65 years in Southern Taiwan. A total of 450 surveys were sent, with 371 receiving a valid response rate of 82.4%. In this study, the analyzed data used the canonical correlation analysis to examine the relationship among variables of this study. The results demonstrated that the linear combination of the two sets of variables yields three significant canonical variates, with only the first having sufficient explanatory power. The results indicate that social support and perceived healthiness are strongly connected. This study contributes to the government, welfare organizations, and academic research institutions with valuable insights for future reference in formulating and implementing welfare policies for the people who aged over 65 years, as well as for conducting subsequent research in this field.